2022
DOI: 10.1029/2021gl096874
|View full text |Cite
|
Sign up to set email alerts
|

Large Surface‐Rupture Gaps and Low Surface Fault Slip of the 2021 Mw 7.4 Maduo Earthquake Along a Low‐Activity Strike‐Slip Fault, Tibetan Plateau

Abstract: Based on field investigations, interpretations of high‐resolution UAV images, and analyses of available InSAR data, we mapped the fault geometry and surface ruptures of the 2021 Mw 7.4 Maduo earthquake that occurred on a low‐activity strike‐slip fault within the Tibetan Plateau. The results indicate that (a) the earthquake activated a fault that is ∼161 km long and has complicated structural geometry; (b) the surface rupture occurs over a distance of 148 km, but is separated into three distinct segments by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 38 publications
8
77
0
Order By: Relevance
“…This means that most of the aftershocks in this region occur along the discrete rupture zone. Field observations of the surface fracture (Yuan et al, 2022) revealed discrete secondary cracks along the F3 segment, but no obvious continuous fracture, which also verified the existence of conjugate secondary faults. Thus, we suggest that the F2 segment of our AFFP model represents a discrete rupture zone or an immature secondary fault that was Frontiers in Earth Science frontiersin.org activated by the coseismic rupture.…”
Section: Complexity Of the Maduo Fault Zonementioning
confidence: 60%
See 1 more Smart Citation
“…This means that most of the aftershocks in this region occur along the discrete rupture zone. Field observations of the surface fracture (Yuan et al, 2022) revealed discrete secondary cracks along the F3 segment, but no obvious continuous fracture, which also verified the existence of conjugate secondary faults. Thus, we suggest that the F2 segment of our AFFP model represents a discrete rupture zone or an immature secondary fault that was Frontiers in Earth Science frontiersin.org activated by the coseismic rupture.…”
Section: Complexity Of the Maduo Fault Zonementioning
confidence: 60%
“…In a strike-slip fault, shear deformation zone contains multiple sets of secondary faults, including secondary faults parallel to the main fault. In the case of the 2021 Maduo earthquake, complex topographic and geomorphic features (e.g., near-surface water and soft sediments; Yuan et al, 2022) may have reduced the positioning accuracy of aftershocks and caused a loss of plane features. As a result, we could not judge whether the aftershock in F2 area occurred on the secondary fault parallel to the main fault or on the secondary fault conjugate to it.…”
Section: Complexity Of the Maduo Fault Zonementioning
confidence: 99%
“…After the 2021 Maduo Earthquake, Yuan et al [2022] used UAV-SfM to take photographs of the surface rupture of the Maduo Earthquake systematically, and quickly obtained the detailed surface rupture distribution and horizontal and vertical displacement distribution maps of the Maduo Earthquake (Yuan et al, 2022). This work has demonstrated great efficiency of UAV in processing post-earthquake emergency data, and also improves the precision and accuracy of coearthquake dislocation measurements.…”
Section: Co-seismic Deformation Detection Using Pre and Post-earthqua...mentioning
confidence: 99%
“…China is one of the most active seismic regions in the world and in recent decades, large-magnitude earthquakes have occurred frequently and abruptly, resulting in serious damage and numerous casualties, such as the 1976 Mw 7.8 Tangshan earthquake (Huang and Yeh, 1997), 2008 Mw 7.9 Wenchuan earthquake) (Xu et al, 2009), and 2021 Mw 7.4 Maduo earthquake (Yuan et al, 2022). Therefore, in China, LiDAR technology and surveys applied to investigate fault activity and earthquake surface deformation are crucial and will improve the country earthquake disaster assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, few studies have considered the faults within active blocks; accordingly, the seismic risk and role in strain partitioning of these faults have generally been neglected. Over the past hundred years, a number of strong earthquakes, such as the 1933 M 7.5 Diexi earthquake (Ren et al, 2018), 1947 M 7¾ Dari earthquake (Liang et al, 2020a), 1948 Ms 7 1 / 4 Litang earthquake (Xu et al, 2005a), and 2021 Mw 7.3 Maduo earthquake (Ren et al, 2022a), have successively occurred along intrablock faults, indicating that the secondary faults within active blocks also exhibit the potential to produce devastating earthquakes and can play a role in strain partitioning (Zhan et al, 2021;Ren et al, 2022b;Yuan et al, 2022). As a consequence, investigation of the rupture behavior of these faults is vital not only to assess the regional seismic potential but also to better understand the deformation mechanism of tectonic blocks (Ren et al, 2013;Sun et al, 2015;Sun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%